Perbandingan Kadar Hemoglobin Ibu Hamil menggunakan Metode Digital dengan Metode Cyanmethemoglobin - Siregar, Mukhlidah Hanun; Koerniawati, Ratu Diah; Sijabat, Agnes Irma Yuliarta; Utami, Hanifa; Nurkhairani, Azzakiyatul (Faletehan Health Journal, 2023)
Low levels of hemoglobin in erythrocytes have an impact on reducing the ability of erythrocytes to carry oxygen throughout body's tissues; thus, the body becomes deprived of oxygen which may cause anemia. Anemia can be identified by carrying out blood tests to determine blood hemoglobin levels from capillary blood samples and venous blood samples. This study was conducted to analyze differences in hemoglobin levels from two methods, namely the digital method from capillary blood samples and the cyanmethemoglobin method from venous blood samples of third trimester pregnant women in Serang City. This study used a quantitative method with a cross-sectional research design. The locations were in three working area of Serang City Health Center, Banten and the sampling technique was purposive. The data were collected from March to May 2023 on 81 pregnant women. The results showed that the average hemoglobin level using the digital method was higher (13.2 g/dL) compared to the cyanmethemoglobin method (11.5 g/dL). In addition, the cyanmethemoglobin method reported more cases of anemia (34.6%) compared to the digital method (8.6%). Pregnant women were suggested to check hemoglobin using cyanmethemoglobin method which has been recommended by the International Committee for Standardization in Hematology.